PROFESSIONAL ETHICS IN THE DIGITAL AGEA MORAL FORTRESS OR A NEW CHALLENGE OF CONFLICT OF INTEREST? - Rahmad Haqqi; Rangga Saputra; Yusnaini (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2026)
Digital transformation has fundamentally reshaped the professional landscape by introducing both efficiencies and complex ethical dilemmas. This study aims to elaborate on the role of professional ethics in the digital era, examining its function as an effective moral fortress as well as its potential to trigger new, unmapped conflicts of interest. Employing a qualitative method, the author conducts a systematic review of contemporary literature on digital ethics, Artificial Intelligence (AI), and data surveillance. The analysis utilizes MacIntyrean Virtue Ethics to examine moral character and Rest’s Four-Component Model to evaluate ethical decision-making processes. The findings reveal a contrasting duality: on one hand, professional ethics serves as a crucial instrument in protecting consumer welfare and public trust within virtual ecosystems; on the other hand, technological acceleration creates gray areas where